2016
DOI: 10.11628/ksppe.2016.19.4.269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Horticultural Activity Based on Self-growth Group Counseling on the Self-esteem, Ego-resilience, and Stress of Adolescents for Educational Welfare

Abstract: The purposes of this study were to examine the factors of psychological maladjustment experienced by adolescents for educational welfare, and to analyze the effects of a self-growth group counseling program applied to horticultural activities, which have been considered effective social alternatives, on adolescents' self-esteem, ego-resilience, and stress change. For these purposes, the program was executed for 8 th-grade students at Y Middle School through 10 sessions, once a week, and 100 minutes per session… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
3
1
0
Order By: Relevance
“…The expectations and curiosity about new plants and activities observed in each session appear to support the problem-solving ability of the participants. This result is in line with those of a previous study where attachment to plants and curiosity in a cultivation-based horticultural therapy program were found to be effective in improving the psychological health of adult prisoners [ 42 ]; in another study, horticultural therapy was effective in improving ego-resiliency by stimulating children’s interest and curiosity [ 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…The expectations and curiosity about new plants and activities observed in each session appear to support the problem-solving ability of the participants. This result is in line with those of a previous study where attachment to plants and curiosity in a cultivation-based horticultural therapy program were found to be effective in improving the psychological health of adult prisoners [ 42 ]; in another study, horticultural therapy was effective in improving ego-resiliency by stimulating children’s interest and curiosity [ 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…This result coincided with the results of earlier studies including those of Nam et al (2010) and Yun and Yoo (2011) on the self-esteem of children; those of Chon (2008), Jeong et al (2010), Kim (2014) and Kong et al (2015) on the selfesteem of the elderly; that of Jeon et al (2016) conducted among adolescents; and that of Son et al (2000) conducted among patients with chronic schizophrenia. However, it did not coincide with the results of the study of Kim et al (1999) that reported no statistically significant difference in selfesteem after offering a supportive group therapy program, and those of the study of Chi (2010) conducted on inmates.…”
Section: Changes In Self-esteemsupporting
confidence: 91%
“…Kang et al (2015) also found that green activities among other leisure activities were effective to reduce the stress and depression of the elderly, and Kwon et al (2011) reported the positive effects of horticultural therapy programs on the depression and stress of hospice care patients. Jeon et al (2016) also confirmed the significant effect of such programs on the self-esteem, ego resiliency and stress of low-income children.…”
Section: ⅰ Introductionsupporting
confidence: 62%
See 1 more Smart Citation